Evaluation of teaching effect of first-aid comprehensive simulation-based education in clinical medical students - Peng, Mian; Su, Ning; Hou, Rui; Geng, Huijuan; Cai, Fangfang; Zhong, Weixiong; Zhang, Weifang; Zhong, Jingxing; Yang, Zhengyue; Cao, Weiling (Frontiers in Public Health, 2022)
Background Although students mastered the composition skills, they lack of the ability to effectively integrate these composition skills in real clinical situations. To address the problem, we set up different levels of situational simulation training for medical students in grades 2–4, and evaluate the teaching effect of first-aid situation comprehensive simulation-based education (SBE) on clinical medical students. Methods The medical students in Grade 2, 3, and 4 received different situational SBE, respectively. The 2nd-year medical students received a single skill module which included cardiopulmonary resuscitation, endotracheal intubation, and electric defibrillation training. The 3rd-year medical students received a single subject module which included cardiovascular and respiratory system training. The 4th-year medical students received the integrated multidisciplinary module which combined first-aid skills, clinical thinking, and teamwork training. The primary outcome was the expert evaluation and peer evaluation. The secondary outcome was students' satisfaction questionnaire response. In our training, we arranged an adequate teaching staff for intensive training and timely feedback (the student–teacher ratio of 5:1), adequate time for repetitive practice (Each SBE was carried out within 4 h), curriculum design, and integration from real cases by clinicians, realistic computer-driven mannequins to ensure simulation fidelity, providing a different difficult level of SBE to different grades of students, and pre- and post-tests for outcome measurement. Results In all of the single skill module, single subject module or comprehensive disciplines module, the scores in the expert evaluation and peer assessment after the training were significantly higher than before the training, and the differences were statistically significant (p < 0.05). The integrated subject training, although having the lowest pre—and post-test marks, had the largest increase in score. Conclusion The first aid comprehensive simulation-based education in grade 2–4 clinical medical students, basing on timely feedback, repetitive practice, curriculum integration, simulation fidelity, and outcome measurement are effective in improving the students' proficiency in managing the real emergencies.